Evaluation of transformer magnetizing core loss - Ahmed, M.A.H.; Soib, Taib; Ismail, Daut; Uthman, S. (Asian Network for Scientific Information, 2009)
http://www.scialert.net/abstract/?doi=jas.2006.2579.2585